ENTREPRENEURSHIP EDUCATIONAL PROGRAMS IN THE MODERN UNIVERSITY - Alexey K. Klyuev; Alexandr A. Yashin (Moscow Polytechnic University, 2016)
The presented paper covers the issues connected with entrepreneurial education formation, implementation and further development in modern university. Based on entrepreneurial activity in Russia data analysis the j udgement about the low level of youth involvement into entrepreneurial activities was produced. Such situation is governed by inadequate educational programs in the sphere of entrepreneurial education, which are being implemented on the all levels of professional education. This paper shows possibilities of creation of multilevel and sustained system of entrepreneurial education, which forms all necessary basic and professional competencies. The authors drew to a conclusion about the importance and the role of soft skills in the process of entrepreneurial education. The effective creation of all necessary entrepreneurial competencies is possible only in the framework of modern innovative educational policies and techniques implementation, namely, the system of majors and minors. Such educational policy is being implemented in Ural Federal University and in the Institute of Public Administration and Entrepreneurship of UrFU nowadays.